تطبيق استراتيجية خريطة التفكير الدائرة في تعليم مهارة الكلام - Basyori, Ahmad; Pertiwi, Intan Ratna; Dinata, Rahmat Satria (Journal of Arabic Language Teaching, 2024)
The educational process needs learning strategies that are characterized by interaction and building thinking skills in learning speaking skills. This study aims to apply the Circle Thinking Map strategy in improving the mastery of Arabic speaking skills among eighth grade students at Nurul Hidayah Islamic Middle School Tanggamus Lampung. This research is a classroom action research. Classroom action research procedures are carried out in a flow called a cycle. Each cycle consists of four phases of activity, namely planning, implementation, observation, and reflection. This classroom action research is planned in two cycles, where data is collected in the form of observations, interviews, and tests. The results obtained from this study are the application of speaking skill learning using the Circle Thinking Map strategy in the first cycle, where the application rate was 52%. In the second cycle, there was a significant increase to 84%. Based on these results, it can be concluded that the application of the Circle Thinking Map strategy improves eighth grade students' ability in speaking skills at Nurul Hidayah Islamic Middle School Tanggamus Lampung.